Asymmetric effects of a leaf‐chewing herbivore on aphid population growth. (5th October 2018) - Davidson‐Lowe, Elizabeth; Szendrei, Zsofia; Ali, Jared G.
Abstract : 1. Plant responses to herbivory are often specific to the feeding guild of the attacking herbivore. These phytochemical responses to herbivore damage can affect herbivore performance and activity. Comprehensive studies on the ecological consequences of multi‐herbivore plant interactions are key to understanding plant–herbivore community dynamics. 2. This study examined how feeding damage by co‐occurring herbivores from separate feeding guilds, Myzus persicae (Sulzer), a sucking herbivore, and Leptinotarsa decemlineata (Say), a chewing herbivore, alter plant chemistry and indirectly affect herbivore performance. Performance was measured when each insect fed on plants individually, sequentially, or simultaneously in laboratory and field experiments. Phytohormone and glycoalkaloid content were measured for each feeding sequence to evaluate plant responses to herbivory by each guild. Mid‐season and end‐of‐season tuber yield were evaluated in the field study. 3. Damage by L. decemlineata negatively impacted M. persicae performance in both laboratory and field settings. Damage by M. persicae did not affect L. decemlineata performance in laboratory assays. However, L. decemlineata performance was positively affected by M. persicae herbivory in the field, but this effect was temporary. Although phytohormones and plant defences varied across treatments, they provide little resolution on interaction outcomes. 4. These results confirm that the presence of multiple feeding guilds on a single plant can affect these chewing and sucking herbivores differentially, but given the variability in our phytochemical analyses compared with other studies, the mechanism remains unclear. The study's findings show that aphids are negatively affected by chewing herbivores across systems, while aphids temporarily affected beetles positively. Abstract : Interactions between co‐occurring herbivores with different feeding strategies asymmetrically affect one another's growth. Aphids are negatively affected by beetle chewing herbivores across systems, while aphids positively affected beetles temporarily. Although phytohormones and plant defences varied significantly across treatments, they provide little resolution on interaction outcomes. Damage by aphids did not affect beetle performance in laboratory assays. However, Leptinotarsa decemlineata performance was positively affected by Myzus persicae herbivory in the field, but this effect was temporary.